Planejamento do uso do solo em unidades de produção familiar produtoras de fumo: limites e possibilidades para a superação de conflitos agroambientais - Pellegrini, João Batista Rossetto (2011)
The occupation of forest ecosystems in mountainous region of the Rio Grande do Sul state occurred with the establishment of agriculture and livestock at small family production units (FPU). Qualitatively and quantitatively scarcity of land has led farmers to explore agricultural areas with no suitability for farming by intensive practices, these areas should be intended to permanent preservation. The present study aims to: a) analyze the agroenvironmental conflicts in agroecosystems of tobacco production arising from inappropriate use of soils, especially in areas of permanent preservation (APP) of riparian forests; b) analyze the importance and limits of the use of environmental legislation instruments (Forest Code) and land classification system for agricultural suitability of soils in agroenvironmental planning as methods for reducing the contamination of water in small FPU; and c) verify the effectiveness of riparian forests in containing the pollution of superficial waters of three landscape units in the Arroio Lino Watershed (ALW). The study area is located in the municipality of Agudo, RS, and covers an area of 480.7 ha, which are subdivided into 36 FPU. The main features of the landscape and land uses were described, quantified and spatialized for the whole ALW and for each of the FPU. The map of APP was obtained by following the orientation of the Brazilian Forest Code. The map of land use conflicts was generated by crossing the layers of current land use, APP and land suitability for agriculture. To evaluate the ability of riparian forests to tamponate the water pollution, samples of water and sediment were collected at different landscape units with a variety of land use and occupation. Samples were taken inside and outside the limits of APP. The results of layers intersection showed that 44% of the ALW have some sort of environmental conflict as a result of inappropriate land use. The conflicts that deserve more attention refer to the occurrence of crops on land unsuitable for agricultural and those located in APP. These sites cover 6.7% of the watershed and constitute the main sources of pollution of surface waters, especially with tobacco being cultivated in the conventional system. Even if cultivating areas are restricted to only 25% of the watershed, an inadequate arrangement of the agricultural plots in the landscape contributes to an increase in up to ten times in water pollution by sediment and phosphorus. Thus, the distribution of land use in the landscape is just as, or even more important than the percentage occupied by each of these uses. Although more than half of ALW area is covered with native forests, the absence of forest cover in the APP, mainly at the edges of streams and water springs, has promoted the transfer of large amounts of sediment and nutrients to the waterways due to erosion by occasion of rain. Even though riparian forests did prove to be effective in containing surface runoff, they are not enough if the adjacent and higher areas of the landscape, such as APP at the top and steep slopes of the hills with soils of low agriculture suitability, are being used intensively. Under the conditions of ALW in which there are strong environmental restrictions and limited arable land, the unrestricted application of environmental legislation, especially of the Forest Code, may result in severe restrictions to several FPU. In a result of this, for the agroenvironmental planning it will be necessary to analyze the characteristics of each FPU in particular and how it integrates with the watershed landscape. A replanning of these FPU is critical to ensure the continuity of agriculture in these environments, while minimizing impacts on water resources. However, it is considered to be unsuitable to preservation and improvement of quality of natural resources, particularly superficial water, the current tobacco production and its technological arrangement. The transition to an agriculture of ecological bases could be the way to overcome the agroenvironmental conflicts in these regions which have strong limitations imposed by the agricultural suitability of land and by environmental legislation.